Educating hospital patients to prevent falls: protocol for a scoping review - Louise Shaw; Hazel Heng; Dana Jazayeri; Debra Kiegaldie; Anne-Marie Hill; Meg E Morris (BMJ Open)
Introduction Falls prevention in hospitals is an ongoing challenge worldwide. Despite a wide variety of recommended falls mitigation strategies, few have strong evidence for effectiveness in reducing falls and accompanying injuries. Patient education programmes that promote engagement and enable people to understand their heightened falls risk while hospitalised are one approach. The aim of this scoping review is to examine the content, design and outcomes of patient education approaches to hospital falls prevention. As well as critiquing the role of patient education in hospital falls prevention, strategies that can be used in clinical practice shall be recommended.Methods and analysis The analysis will apply the methodological framework developed by Arksey and O’Malley and refined by the Joanna Briggs Institute. An initial limited search of Cumulative Index to Nursing and Allied Health Literature (CINAHL) and PubMed will be completed to identify keywords and index terms. A developed search strategy of Medical Subject Headings and text words will be conducted of PubMed, CINAHL, Cochrane Central Register of Controlled Trials, Allied and Complementary Medicine Database, PsychINFO, Education Resources Information Center and grey literature databases from January 2008 to current. The reference lists of included articles will be hand searched for additional studies. Two reviewers will screen the titles and abstracts independently and analyse the full text of potential articles based on the inclusion and exclusion criteria. The data will be extracted using a structured data form. Thematic analysis and numerical synthesis of the data will be conducted, and key themes will be identified.Ethics and dissemination Results of this scoping review will illuminate the designs and outcomes of patient education research for hospital falls prevention in the current literature. It is anticipated that the findings will highlight best-practice educational design to inform the development of future patient-focused education for falls prevention. Study findings will be presented at relevant conferences and public forums, and published in peer-reviewed journals. Ethics approval is not required.